2015
DOI: 10.1179/1743281215y.0000000009
|View full text |Cite
|
Sign up to set email alerts
|

Study on CCD laser scanning flatness measurement method for hot rolled strip

Abstract: To provide a flexible calibration method and make an accurate machine vision (MV) based flatness measurement strategy a reality in routine production line, an area scan charge coupled device (CCD) laser stripe scanning approach is presented. The applicability of the proposed method is not tied to the strip exclusively. First, we devise an automatic laser stripe imaging quality evaluation method through analysing the characteristics of the image grey gradient of laser stripe, which is a prerequisite for precise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Liu et al [32] proposed a method based on flame image processing and pattern classification for end-point prediction in the basic oxygen furnace (BOF). Zhao et al [33] suggested a method using region-scanning charge-coupled device (CCD) laser stripe scanning to measure large field-of-view visualizations based on MV in modern steel production lines. Additionally, scholars have discussed the application of intelligent logistics systems to achieve accurate tracking and optimization of raw materials, thereby reducing costs and improving production efficiency [34,35].…”
Section: Intelligent Application Of Steelmaking Processmentioning
confidence: 99%
“…Liu et al [32] proposed a method based on flame image processing and pattern classification for end-point prediction in the basic oxygen furnace (BOF). Zhao et al [33] suggested a method using region-scanning charge-coupled device (CCD) laser stripe scanning to measure large field-of-view visualizations based on MV in modern steel production lines. Additionally, scholars have discussed the application of intelligent logistics systems to achieve accurate tracking and optimization of raw materials, thereby reducing costs and improving production efficiency [34,35].…”
Section: Intelligent Application Of Steelmaking Processmentioning
confidence: 99%
“…Another flatness measuring method is to use a CCD (charge coupled device) camera as a data acquisition instrument and to process the acquired image data to obtain the flatness. The data processing process is relatively complex [12]. Furthermore, an instrument developed based on the laser ranging method [13] is also an option.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in hot-rolled strip flatness measurement system, the measurement error is related to the process signal. When the vibration signal caused by the movement of hot-rolled strip is independent of the system, it can be considered as white Gaussian noise [16]. But it will lead to measurement error, when we get it by the system.…”
Section: Introductionmentioning
confidence: 99%